A CASE REPORT: PHYSIOLOGICAL MECHANISM OF MEDOVRIDDHI WITH ITS AYURVEDIC INTERVENTION - PRATIMA GUPTA; VAIDEHI VINAY RAOLE (The Bioscan, 2025)
The human body is composed of three doshas, seven dhatus (body tissues), and three malas, with the balanced state known as Swastha (health)1. Among the seven dhatus, Meda dhatu (adipose tissue) plays a key role in maintaining oleation, regulating perspiration, and contributing to the body's overall strength1. However, when Meda dhatu becomes vitiated due to improper dietary habits and a sedentary lifestyle, it leads to metabolic disorders, particularly obesity, diabetes mellitus, and polycystic ovary disease (PCOD). Obesity, defined in Ayurveda as medo vriddhi or sthaulya, is linked to numerous non-communicable diseases (NCDs), including heart disease, stroke, type 2 diabetes, osteoarthritis, and certain cancers (endometrial, breast, ovarian, prostate, liver, gallbladder, kidney)2. This case study examines the Ayurvedic view of obesity, its association with various metabolic disorders, and its impact on overall health as identified by both traditional and modern perspectives. A 55-year-old female patient diagnosed with Class 1 obesity (BMI of 32.9 kg/m²)3, and osteoarthritis, treated at KVG Ayurveda Medical College, Sullia, through an Ayurvedic Medohara regimen. The treatment included ruksha (drying) and apatarpana (reductive)4 therapies within the context of Panchakarma, along with dietary modifications and therapeutic yoga. This holistic approach aims to reduce excess body fat and alleviate symptoms of osteoarthritis while promoting overall well-being.